Trace element levels in whole blood of riparian villagers of the Brazilian Amazon - Rodrigues, Jairo Lisboa; Batista, Bruno Lemos; Fillion, Myriam; Passos, Carlos J.S.; Mergler, Donna; Barbosa, Fernando (The Science of the total environment, 2009)
Monitoring the nutritional status of essential elements is of critical importance in human health. However, trace element concentrations in biological fluids are affected by environmental and physiological parameters, and therefore considerable variations can occur between specific population subgroups. Brazil is a large country with much food diversity. Moreover, dietary habits differ from north to south. As an example, the traditional populations of the Brazilian Amazon basin are heavily dependent on fish, fruits, vegetables and manioc for their daily sustenance. However, very few studies have examined to what extent these diets reflect adequate nutritional status for essential elements. Then, in the present study we have evaluated the levels of some trace elements (Cu, Co, Zn Sr, and Rb) in the whole blood of a riparian Brazilian Amazonian population and estimated the influence of age and gender on levels and inter-element interactions in the same population. For this, 253 subjects, aged 15 to 87, from 13 communities situated on the banks of the Tapajós, one of the major tributaries of the Amazon, were randomly selected. The values found for cobalt, copper and strontium in whole blood are in the same range as in other populations. On the other hand, the levels of rubidium and zinc may be considered higher. Moreover, gender was shown to influence Zn and Cu levels while age influenced the concentrations of Sr and Rb in men and Cu in women. Given the scarcity of studies examining nutritional status in traditional communities of the Amazon, our study is the first to provide relevant insight into trace element values in this region and inter-element interactions. This paper is also of particular importance for future studies looking at the possible protective effects of traditional Amazon riparian diets against mercury intake from fish consumption.